Outcomes After Direct Thrombectomy or Combined Intravenous and Endovascular Treatment Are Not Different. Issue 2 (February 2017) - Abilleira, Sònia; Ribera, Aida; Cardona, Pedro; Rubiera, Marta; López-Cancio, Elena; Amaro, Sergi; Rodríguez-Campello, Ana; Camps-Renom, Pol; Cánovas, David; de Miquel, Maria Angels; Tomasello, Alejandro; Remollo, Sebastian; et al.
Abstract : Background and Purpose—: Whether intravenous thrombolysis adds a further benefit when given before endovascular thrombectomy (EVT) is unknown. Furthermore, intravenous thrombolysis delays time to groin puncture, mainly among drip and ship patients. Methods—: Using region-wide registry data, we selected cases that received direct EVT or combined intravenous thrombolysis+EVT for anterior circulation strokes between January 2011 and October 2015. Treatment effect was estimated by stratification on a propensity score. The average odds ratios for the association of treatment with good outcome and death at 3 months and symptomatic bleedings at 24 hours were calculated with the Mantel–Haenszel test statistic. Results—: We included 599 direct EVT patients and 567 patients with combined treatment. Stratification through propensity score achieved balance of baseline characteristics across treatment groups. There was no association between treatment modality and good outcome (odds ratio, 0.97; 95% confidence interval, 0.74–1.27), death (odds ratio, 1.07; 95% confidence interval, 0.74–1.54), or symptomatic bleedings (odds ratio, 0.56; 95% confidence interval, 0.25–1.27). Conclusions—: This observational study suggests that outcomes after direct EVT or combined intravenous thrombolysis+EVT are not different. If confirmed by a randomized controlled trial, it may have a significant impact on organization of stroke systems of care. Abstract : Supplemental Digital Content is available in the text.